Köhler's Theory and Inquiry Learning: Literature Review of 21st Century Theoretical Implications - Aisha Shafa Kirana; Naufal Fais Rahman; Suparmi (Yayasan Cerdas Pedia Indonesia, 2026)
Despite global educational mandates to cultivate modern competencies, inquiry learning frequently degrades into superficial guessing due to inadequate cognitive scaffolding during inevitable student impasses. To address this theoretical void, this qualitative study employs a systematic literature review adhering strictly to the PRISMA framework to synthesize Wolfgang Köhler’s Gestalt theory of insight with constructivist pedagogical architectures. Analyzing interdisciplinary literature from psychology and education, findings reveal that cognitive roadblocks and epistemic emotions are not instructional failures, but rather necessary incubation mechanisms triggering sudden representational restructuring, known universally as the insight moment. By mapping internal cognitive phases directly onto external pedagogical stages, this research demonstrates how deliberately engineering productive struggle operationalizes the robust development of critical thinking and creativity. Ultimately, this integrated framework provides a rigorous neurocognitive justification for progressive educational policies like Indonesia’s Kurikulum Merdeka while simultaneously establishing vital ethical boundaries against premature artificial intelligence integration within modern global learning environments today.